ASSOCIATION OF DIFFERENT PARAMETERS OF COMPLETE BLOOD COUNT WITH SEVERITY AND PROGNOSIS OF GUILLAIN-BARRE SYNDROME - Aziz, Nauman; Khan, Humera; Jafri, Syeda Rizwana; Qureshi, Fauzia; Muneeb, Amna; Akif, Ursula (Pakistan Armed Forces Medical Journal, 2021)
Objective: Guillain-barré syndrome is the most common and most severe acute paralytic neuropathy. This study is also aimed at to know that if there is any association of parameters of complete blood count and whether these can be used as a prognostic marker for guillain-barré syndrome. Study Design: Retrospective cross-sectional. Place and Duration of Study: Sahiwal Medical College Sahiwal, from Oct 2019 to Aug 2020. Methodology: This retrospective cross-sectional study was conducted at Sahiwal Medical College Sahiwal, from Oct 2019 to Aug 2020 after approval from Institutional Review Board. The data was assessed by SPSS-26. Frequency distributions of study participants were calculated. Significance of the associations was assessed by Kruskal-Wallis test and one way ANOVA test. A p-value <0.05 was taken as statistically significant. Results: Male were predominant among guillain-barré syndrome patients presenting at DHQ Hospital, Govt. Haji Abdul Qayyum Hospital Sahiwal and Surayya Azeem Teaching Hospital Lahore (65.2%). Most of the patients were in the mild category of guillain-barré syndrome (60.8%), 26% in moderate and 14.2% in severe category. We also calculated complete blood count of all study participants and calculated normality of data. We made two tables depending upon the normality of the data and cross tabulated them with severity of guillain-barré syndrome. The parameters with skewed distribution cross tabulated with severity of guillain-barré syndrome. Platelets counts showed highly significant results (p=0.04). Among the variables which were normally distributed, red blood cell count showed highly significant results when compared with severity of guillain-barré syndrome (p=0.02). Conclusion: There is strong association of some parameters of complete blood count and these can also be used as prognostic markers in severity of guillain-barré syndrome though a more detailed study with larger sample size is needed.